Аналіз адекватності відтворення символіки вірша Емілі Дікінсон «The Soul selects her own Society» у перекладі (на матеріалі українського перекладу В. Кикотя та російського перекладу Б. Львова) - Панасенко, Катерина Олександрівна; Panasenko, K. O. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано відтворення символів вірша Е. Дікінсон «The Soul selects her own Society» в українському і російському перекладах В. Кикотя і Б. Львова, що належить до актуальних питань перекладознавства. Завдання статті полягають у виділенні, декодуванні символів вірша при здійсненні перекладознавчого аналізу тексту оригіналу з текстами перекладів, що стало новим кроком у вивченні рецепції творчості поетеси носіями вказаних мов й уможливило встановити неадекватне відтворення символів вірша у перекладах. The article deals with the problem of reproducing symbolism of the poem «The Soul selects her own Society» by E. Dickinson in Ukrainian and Russian translations, being a crucial issue in translation science. The tasks of the article consist in selecting and decoding symbols of the poem and in performing comparative analysis of the source text and two target texts so that to establish the adequacy level of reproducing symbols in the latter. The analysis is a new step in studies of E. Dickinson’s artistic legacy perception by Ukrainian and Russian native speakers. It has become possible to conclude that both Ukrainian and Russian translations of the poem have certain drawbacks including the change of modality while reproducing symbolic context of the original text, non-recognition of symbols and disregard for units carrying or implying a symbolic meaning. Both translators failed to achieve adequacy while reproducing symbols; playing a very important role in the poem.
Her Own Society» by Emily Dickinson in Translation (on the Basis of Ukrainian and Russian Translations by V. Kykot and B. Lvov)
Keywords: переклад; translation; адекватність; adequacy; символ; symbol